Silences and Accents in the Construction of Gender Violence as a Social Problem in Quito - Paz Guarderas Albuja (Íconos)
Gender violence has been constructed as a social problem in diverse semiotic-material matrices. This article describes these matrices and analyzes their effects on laws and municipal services in Quito, Ecuador. Five different matrices are examined: sexuality, health, human rights; security and disciplinary practices. The analysis demonstrates that the actors and voices that attempted to generate ruptures in the status quo have been silenced, while those that have perpetuated the patriarchal order have become hegemonic.